Effect of H2/CO addition on soot formation in ethylene diffusion flame - Zhang, Yindi; Xue, Yijing; Xu, Zichun; Zeng, Fanjin; Xin, Yue; Chen, Qinghai; Takyi, Shadrack Adjei (Frontiers in Energy Research, 2024)
Coupling the San Diego gas phase reaction mechanism and the Moss Brookes soot model using FLUENT14.0 software, the effect of adding H2/CO on the fuel side on soot formation in an ethylene/air laminar diffusion flame was studied. A specific analysis was conducted on the effects of H2, CO and its chemical effects on flame temperature, soot volume fraction, mole fractions of important intermediate products OH, H, and C2H2, as well as rate of soot mass nucleation, surface growth, and oxidation. In the numerical calculation, the virtual substances FH2 and FCO are set to separate the chemical effect of H2 and CO and to analyze the chemical effect of adding H2 and CO on soot formation. The results show that the flame temperature increases slightly, and the soot volume fraction decreases monotonically with adding H2 and CO. The chemical effect of H2 increases the temperature, the mole fraction of C2H2 and H, the soot nucleation rate, and the surface growth rate, and finally, it promotes soot formation. The chemical effect of CO increases the temperature and H mole fraction, reduces the OH mole fraction, and then increases the soot surface growth rate and reduces the soot oxidation rate. The higher soot nucleation, surface growth rate, and lower oxidation rate jointly promote soot formation.